2010
DOI: 10.1128/aac.00134-10
|View full text |Cite
|
Sign up to set email alerts
|

Global Spread of the hyl Efm Colonization-Virulence Gene in Megaplasmids of the Enterococcus faecium CC17 Polyclonal Subcluster

Abstract: Enterococcus faecium has increasingly been reported as a nosocomial pathogen since the early 1990s, presumptively associated with the expansion of a human-associated Enterococcus faecium polyclonal subcluster known as clonal complex 17 (CC17) that has progressively acquired different antibiotic resistance (ampicillin and vancomycin) and virulence (esp Efm , hyl Efm , and fms) traits. We analyzed the presence and the location of a putative glycoside hydrolase hyl Efm gene among E. faecium strains obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 51 publications
2
57
0
2
Order By: Relevance
“…Hyl gene is translated into hyaluronidase protein acting as a pathogenic factor in Streptococcus pyogenens, Staphylococcus aureus, and Streptococcus pneumoniae [26], and commonly found in spreading disease causing organisms [11]. Especially in recent study in Spain E. faecium with hyl gene was reported to belong to CC17 polyclonal subcluster, which proved the relationship between CC17 and hyl gene [24]. In this study, it was found all 37 isolates had esp gene, and most of isolates (32 isolates, 86.5%) except 5 (CNS16, CBS3, CBS6, CBS9, EJS4) had hyl gene.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Hyl gene is translated into hyaluronidase protein acting as a pathogenic factor in Streptococcus pyogenens, Staphylococcus aureus, and Streptococcus pneumoniae [26], and commonly found in spreading disease causing organisms [11]. Especially in recent study in Spain E. faecium with hyl gene was reported to belong to CC17 polyclonal subcluster, which proved the relationship between CC17 and hyl gene [24]. In this study, it was found all 37 isolates had esp gene, and most of isolates (32 isolates, 86.5%) except 5 (CNS16, CBS3, CBS6, CBS9, EJS4) had hyl gene.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the fact that it can be transmitted with vanA resistance gene is believed to make contribution to wide spread of pathogenic VRE [23]. Currently there have been many reports about another pathogenic gene, hyl gene in addition to esp gene [24][25][26]. Hyl gene is translated into hyaluronidase protein acting as a pathogenic factor in Streptococcus pyogenens, Staphylococcus aureus, and Streptococcus pneumoniae [26], and commonly found in spreading disease causing organisms [11].…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, we described a large single-strain outbreak of vanB E. faecium across several hospitals in Western Australia (17). Characterized as CC17 ST173 (34), once eradicated from the hospital environment this strain has not subsequently been isolated in Western Australia, nor was it detected in the AESOP 2011 bacteremia study. Furthermore, failure to isolate ST173 during long-term follow-up screening of previously colonized patients suggests the strain no longer had a selective advantage once outside the hospital environment.…”
Section: Discussionmentioning
confidence: 99%
“…It includes representative isolates of VRE recovered from swine and healthy humans in national surveillance studies conducted in Portugal and Denmark (1995 to 2008) (references 17,26,35,37, and 38 and this study), strains widespread among swine from Switzerland and Spain (5,22), and the first VRE isolates recently recovered from animals in the United States (11). For comparison, we included a large and well-typed collection of clinical VRE isolates (140 E. faecium and 50 E. faecalis isolates) recovered from 23 countries, including Portugal, Spain, Denmark, and the United States, during the last 3 decades, most of which had caused hospital outbreaks (12,16). Testing of susceptibility to 12 antibiotics was performed either by E strip (bioMérieux, Solna, Sweden) or by a standard agar dilution method following recommended guidelines of the manufacturer or CLSI (6).…”
Section: Methodsmentioning
confidence: 99%